A Review on Question Answering Systems: Domains, Modules, Techniques and Challenges. - Maram K. ALMOTAIRI1; Fethi FKIH2 (Communications of International Proceedings, 2021)
With the rapid technological development and the availability of a huge amount of data on the internet, querying information content has become growingly important. Therefore, Question Answering systems play a basic role in information retrieval text processing and information extraction. Question Answering systems are referred to as intelligent systems, that aim to answer specific questions in natural language in order to satisfy users. Question Answering system has many applications based on the source of answers. In this paper, we provide the main domains of the Question Answering system. And we identify the Question Answering techniques, as well as the Challenges when building or improving this system. Our method was based on discussing the approaches that were used in previous related researches.
Keywords: Question Answering System; Information Retrieval; Ontology; Natural Language Processing.